The practice Baranowitz Kronenberg Architecture - Vandeputte, Tom 1983-; Lixenberg, Dana 1964- (Architectura & Natura, 2013)
This monograph documents the holistic nature of the design philosophy established by Tel Aviv-based architects Irene Kronenberg and Alon Baranowitz, where space, form and materials are expressly employed to enhance human experience and social interaction. Incorporating culture, time and place in the design process is fundamental to their approach. In this book, the architects offer a personal analysis of the thinking behind seven of their projects, illustrated by extensive plans, models and photos. Included are the Tel Aviv restaurants Jaffa Tel Aviv and Deca, the Israel Museum shop, Amsterdam's Palace Hotel and Sir Albert Hotel and Izakaya, and Villa Pi